Pharmacological Applications of Bile Acids and Their Derivatives in the Treatment of Metabolic Syndrome - Ðanić, Maja; Stanimirov, Bojan; Pavlović, Nebojša; Goločorbin-Kon, Svetlana; Al-Salami, Hani; Stankov, Karmen; Mikov, Momir (Frontiers in Pharmacology, 2018)
Apart from well-known functions of bile acids in digestion and solubilization of lipophilic nutrients and drugs in the small intestine, there is emerging evidence in the past decade that have pointed to the role of bile acids as signaling, endocrine molecules that regulate the glucose, lipid, and energy metabolism through complex and intertwined pathways that are largely mediated by activation of nuclear farnesoid X receptor (FXR) and cell surface G protein-coupled receptor 1, TGR5 (also known as GPBAR1). Interactions of bile acids with the gut microbiota that result in altered composition of bile acids pool, gut microbiota composition and modified signaling pathways, are further extending the complexity of their biological functions. Thus, bile acids signaling pathways have become attractive targets for the treatment of various metabolic diseases and metabolic syndrome opening the new potential avenue in its treatment. In addition, there is a significant effort to unveil some specific properties of bile acids relevant to their potency and selectivity for particular receptors and to design novel modulators of these receptors with improved pharmacokinetic and pharmacodynamic profiles. This resulted in synthesis of few semi-synthetic bile acids derivatives such as 6α-ethyl-chenodeoxycholic acid (obeticholic acid, OCA), norursodeoxycholic acid (norUDCA), and 12-monohetocolic acid (12-MKC) that are proven to have positive effect in metabolic and hepato-biliary disorders. This review presents an overview of the current knowledge related to bile acids implications in glucose, lipid and energy metabolism as well as potential application of bile acids in metabolic syndrome treatment with future perspectives.